Synbiotic Food Consumption Reduces Levels of Triacylglycerols and VLDL, but not Cholesterol, LDL, or HDL in Plasma from Pregnant Women. Issue 2 (23rd November 2013) - Taghizadeh, Mohsen; Hashemi, Teibeh; Shakeri, Hossein; Abedi, Fatemeh; Sabihi, Sima‐Sadat; Alizadeh, Sabihe‐Alsadat; Asemi, Zatolla
Abstract: To our knowledge, no reports are available indicating the effects of synbiotic food consumption on blood lipid profiles and biomarkers of oxidative stress among pregnant women. This study was conducted to evaluate the effects of daily consumption of a synbiotic food on blood lipid profiles and biomarkers of oxidative stress in pregnant women. This randomized, double‐blind, controlled clinical trial was performed among 52 primigravida pregnant women, aged 18 to 35‐year‐old at their third trimester. After a 2‐week run‐in period, subjects were randomly assigned to consume either a synbiotic ( n = 26) or control food ( n = 26) for 9 weeks. The synbiotic food consisted of a probiotic viable and heat‐resistant Lactobacillus sporogenes (1 × 10 7 CFU) and 0.04 g inulin (HPX)/g as the prebiotic. Patients were asked to consume the synbiotic and control foods two times a day. Biochemical measurements including blood lipid profiles, plasma total antioxidant capacity (TAC) and total glutathione (GSH) were conducted before and after 9 weeks of intervention. Consumption of a synbiotic food for 9 weeks resulted in a significant reduction in serum TAG ( P = 0.04), VLDL ( P = 0.04) and a significant rise in plasma GSH levels ( P = 0.004) compared to the control food. No significant effects of the synbiotic food consumption on serum TC, LDL, HDL and plasma TAC levels ( P > 0.05) were observed. Trial registry code:http://www.irct.ir . IRCT201212105623N3.